Evolution of community health workers: the fourth stage - Mor, Nachiket; Ananth, Bindu; Ambalam, Viraj; Edassery, Aquinas; Meher, Ajay; Tiwari, Pearl; Sonawane, Vinayak; Mahajani, Anagha; Mathur, Krisha; Parekh, Amishi; Dharmaraju, Raghu (Frontiers in Public Health, 2023)
Introduction Comprehensive primary care is a key component of any good health system. Designers need to incorporate the Starfield requirements of (i) a defined population, (ii) comprehensive range, (iii) continuity of services, and (iv) easy accessibility, as well as address several related issues. They also need to keep in mind that the classical British GP model, because of the severe challenges of physician availability, is all but infeasible for most developing countries. There is, therefore, an urgent need for them to find a new approach which offers comparable, possibly even superior, outcomes. The next evolutionary stage of the traditional Community health worker (CHW) model may well offer them one such approach. Methods We suggest that there are potentially four stages in the evolution of the CHW – the health messenger, the physician extender, the focused provider, and the comprehensive provider. In the latter two stages, the physician becomes much more of an adjunct figure, unlike in the first two, where the physician is at the center. We examine the comprehensive provider stage (stage 4) with the help of programs that have attempted to explore this stage, using Qualitative Comparative Analysis (QCA) developed by Ragin. Starting with the 4 Starfield principles, we first arrive at 17 potential characteristics that could be important. Based on a careful reading of the six programs, we then attempt to determine the characteristics that apply to each program. Using this data, we look across all the programs to ascertain which of these characteristics are important to the success of these six programs. Using a truth table, we then compare the programs which have more than 80% of the characteristics with those that have fewer than 80%, to identify characteristics that distinguish between them. Using these methods, we analyse two global programs and four Indian ones. Results Our analysis suggests that the global Alaskan and Iranian, and the Indian Dvara Health and Swasthya Swaraj programs incorporate more than 80% (> 14) of the 17 characteristics. Of these 17, there are 6 foundational characteristics that are present in all the six stage 4 programs discussed in this study. These include (i) close supervision of the CHW; (ii) care coordination for treatment not directly provided by the CHW; (iii) defined referral pathways to be used to guide referrals; (iv) medication management which closes the loop with patients on all the medicines that they need both immediately and on an ongoing basis (the only characteristic which needs engagement with a licensed physician); (v) proactive care: which ensures adherence to treatment plans; and (vi) cost-effectiveness in the use of scarce physician and financial resources. When comparing between programs, we find that the five essential added elements of a high-performance stage 4 program are (i) the full empanelment of a defined population; (ii) their comprehensive assessment, (iii) risk stratification so that the focus can be on the high-risk individuals, (iv) the use of carefully defined care protocols, and (v) the use of cultural wisdom both to learn from the community and to work with them to persuade them to adhere to treatment regimens.